Five-year follow-up of endoscopic resection of symptomatic os trigonum: a prospective interventional cohort study of a possible cause of ankle and big toe pain. Issue 6 (November 2021) - Rakha, Mohamed; Sallam, Asser
Abstract : Background: The authors aimed to evaluate the functional outcomes of endoscopic resection and debridement of symptomatic os trigonum and associated inflammatory changes including the flexor hallucis longus (FHL) pathologies. Methods: A prospective interventional study was conducted including 28 patients with 32 symptomatic os trigonum in the period from January 2010 to March 2016. The mean age of patients was 23.6 yr (range, 12 to 45 yr). All patients completed a minimum follow-up of 5 yr. Outcomes were assessed by the 100-mm visual analogue scale (VAS), American Orthopedic Foot and Ankle Society score (AOFAS), and the postoperative complication rate. Results: Endoscopic examination revealed tibiotalar and subtalar hypertrophic synovitis in 14/32 and 13/32 patients, respectively. A small bony prominence encroached upon the FHL in 3/32 patients, 18/32 patients had FHL tenosynovitis, and the FHL tendon was constricted at its entry point into the tarsal tunnel requiring release of the flexor retinaculum in one patient. The mean AOFAS and the VAS scores significantly improved at final follow-up. The degree of improvement of AOFAS and the VAS scores was greater for the posterior ankle impingement group than the os trigonum fracture group. All patients experienced no major complications. Conclusions: Posterior endoscopic excision of a symptomatic os trigonum is safe, feasible, and has excellent results in patients with various sporting or occupational activities. The degree of improvement is greater for patients without os trigonum fracture. Level of Evidence: Level IV.